Optimized versus corrected peak power during friction-braked cycle ergometry in males and females - James, D. V. B.; Wood, D. M.; Maberly, T. C. B.; de Ste Croix, M. (Journal of Sports Sciences, 2007)
The aim of this study was to compare optimization and correction procedures for the determination of peak power output during friction-loaded cycle ergometry. Ten male and 10 female sports students each performed five 10-s sprints from a stationary start on a Monark 864 basket-loaded ergometer. Resistive loads of 5.0, 6.5, 8.0, 9.5, and 11.0% body weight were administered in a counterbalanced order, with a recovery period of 10 min between sprints. Peak power was greater and occurred earlier, with less work having been done before the attainment of peak power, when the data were corrected to account for the inertial and frictional characteristics of the ergometer. Corrected peak power was independent of resistive load (P > 0.05), whereas uncorrected peak power varied as a quadratic function of load (P < 0.001). For males and females, optimized peak power (971 ± 122 and 668 ± 37 W) was lower (P < 0.01) than either the highest (1074 ± 111 and 754 ± 56 W respectively) or the mean (1007± 125 and 701 ± 45 W respectively) of the five values for corrected peak power. Optimized and mean corrected peak power were highly correlated both in males (r = 0.97, P < 0.001) and females (r = 0.96, P < 0.001). The difference between optimized and mean corrected peak power was 37 ± 30 W in males and 33 ± 14 W in females, of which approximately 15 W was due to the correction for frictional losses. We conclude that corrected peak power is independent of resistive load in males and females.